Resilencia y su infuencia en el tratamiento de las personas con quemaduras del Hospital General Isidro Ayora en la ciudad de Loja - Ortega Ortega, Stefany Giset (2018)
Burns are one of the most traumatic injuries a person can experience, having to overcome an accident and being hospitalized for recovery are situations that the person has to face. The objective of this research was to analyze the level of resilience of burn patients during their treatment at the Isidro Ayora General Hospital in the city of Loja. It was a qualitative-quantitative, descriptive-analytical and transversal study. For the collection of the information, a data record taken from the patient's medical history was used, where the identification data and its clinical assessment were obtained. In addition, the resilience scale of Wagnild and Young was applied to measure the level of resilience, the sample consisted of 30 patients with burns. The data obtained showed that 53.3% of the patients have a high level of resilience and are those who remained hospitalized for two weeks; 16.7% have moderate resilience, the length of time they were hospitalized was two weeks; and, 30% have a low level of resilience, which were hospitalized for four weeks. It was concluded that the majority of patients who have a high level of resilience, their wound evolves and recovers in a minimum time of two weeks. Therefore, a psychoeducation plan was recommended to all patients with a high or low level of resilience so that it is strengthened and they can better face the adversity for which they lived. Keywords: resilience, burns, Burn Unit, psychoeducation